A mobile app for ESL understanding sexism in the English language / Mohd Taufik Mishan … [et al.] - Mishan, Mohd Taufik; Ibrahim, Syazliyati; Hassan, Asrol; Andin Salamat, Azni Syafena; Mohammed, Syakirah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
One of the effects of living in a globalised world is the disparity between men and women is getting smaller. This happens because both genders strive in numerous ways to seek better understanding of one another in many areas including language. English language is known to be a gendered language. This notion of English being a gendered language can easily escape second language users especially in Malaysia because the main languages used in this country are not gendered. Hence, to educate second language users, a mobile app is developed to expose them to the elements of sexism in the English language. Since smartphones today are very common among Malaysians from all walks of life, creating a user-friendly mobile app which is just a fingertip away can truly be helpful. By educating second language users about sexism in the English language, the younger generation will be more polite, considerate and respectful of one another.